All-solid-state battery

CN123036699APending Publication Date: 2026-11-03SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580024977.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-24
Filing Date
2025-02-17
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing lithium-ion batteries use electrolytes containing flammable organic solvents, which pose a risk of overheating and fire during short circuits. Furthermore, traditional all-solid-state batteries are difficult to adapt to the diverse shape requirements of wearable electronic devices.

Method used

An all-solid-state battery was designed, including a stack, a first external electrode, and a second external electrode. The stack consists of a positive electrode layer, a solid electrolyte layer, and a negative electrode layer. The stack is bent in a second direction and has curvature. The external electrode is connected to the end surface of the stack, and an insulating layer is provided on the outside to improve safety and adaptability.

Benefits of technology

It enables safe and reliable battery installation in ring-shaped wearable electronic devices, reduces the risk of thermal runaway, adapts to various shape requirements, and improves the applicability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123036699A_ABST
    Figure CN123036699A_ABST
Patent Text Reader

Abstract

A kind of all-solid-state battery includes laminated body, the laminated body includes the positive electrode layer, solid electrolyte layer and negative electrode layer stacked in first direction.The first outer electrode is connected to the positive electrode layer and is arranged on the laminated body, and the second outer electrode is connected to the negative electrode layer and is arranged on the laminated body.The positive electrode layer includes positive electrode current collector and positive electrode active material layer with the solid electrolyte layer contact, and the negative electrode layer includes negative electrode current collector and negative electrode active material layer with the solid electrolyte layer contact.The laminated body is bent in second direction intersecting with the first direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to an all-solid-state battery. Background Technology

[0002] Currently, commercially available lithium-ion batteries use electrolytes containing flammable organic solvents, posing a risk of overheating and fire during short circuits. Therefore, all-solid-state batteries using solid electrolytes instead of electrolyte solutions have been proposed.

[0003] Wearable electronic devices have become increasingly popular, creating a need for all-solid-state batteries that can be installed in wearable electronic devices of various shapes. Summary of the Invention

[0004] Technical issues This disclosure aims to provide an all-solid-state battery that can be installed in a ring-shaped wearable electronic device.

[0005] However, the purpose of this disclosure is not limited to the foregoing purposes and may be extended in various ways within the spirit and scope of this disclosure.

[0006] Solution to the problem An all-solid-state battery may include: a stack comprising a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in a first direction; a first external electrode disposed outside the stack and connected to the positive electrode layer; and a second external electrode disposed outside the stack and connected to the negative electrode layer, wherein the positive electrode layer may include a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer being disposed on the positive electrode current collector and in contact with the solid electrolyte layer, wherein the negative electrode layer may include a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer being disposed on the negative electrode current collector and in contact with the solid electrolyte layer, and wherein the stack is bent in a second direction intersecting the first direction.

[0007] The laminate may have curvature.

[0008] The laminate may include a first surface and a second surface disposed opposite to each other in the second direction, the first surface may have a first radius of curvature and the second surface may have a second radius of curvature.

[0009] The first radius of curvature may be smaller than the second radius of curvature.

[0010] When viewed along the first direction, the first surface and the second surface may be in the shape of a circular arc or an elliptical arc.

[0011] When viewed along the first direction, the first surface and the second surface may form part of a concentric circle.

[0012] The positive electrode layer, the solid electrolyte layer, and the negative electrode layer may each have a curvature corresponding to the laminate.

[0013] The laminate may include a first end surface and a second end surface disposed opposite to each other in a third direction, the third direction intersecting both the first direction and the second direction and extending between the first surface and the second surface, the first external electrode being disposed on the first end surface, and the second external electrode being disposed on the second end surface.

[0014] The laminate may include a third surface and a fourth surface disposed opposite to each other in the first direction, the first external electrode may extend from the first end surface to cover a portion of the third surface and a portion of the fourth surface, and the second external electrode may extend from the second end surface to cover a portion of the third surface and a portion of the fourth surface.

[0015] The laminate may include: a first end surface and a second end surface, disposed opposite to each other in a third direction, the third direction intersecting both the first direction and the second direction and extending between the first surface and the second surface; and a third surface and a fourth surface, disposed opposite to each other in the first direction, the first external electrode may include a first connecting portion disposed on the first end surface and a first lead-out portion connected to the first connecting portion and disposed on the fourth surface, and the second external electrode may include a second connecting portion disposed on the second end surface and a second lead-out portion connected to the second connecting portion and disposed on the fourth surface.

[0016] The all-solid-state battery may further include: a first insulating layer covering the first connection portion on the first end surface; and a second insulating layer covering the second connection portion on the second end surface. The all-solid-state battery according to an embodiment can be installed in a ring-shaped wearable electronic device. Attached Figure Description

[0017] Figure 1 This is a schematic perspective view of an all-solid-state battery according to an embodiment.

[0018] Figure 2 It is shown Figure 1 A top view of an all-solid-state battery.

[0019] Figure 3 It is shown schematically. Figure 1 A three-dimensional diagram of a stacked structure.

[0020] Figure 4 It is shown schematically. Figure 1 The front view of the stacked body.

[0021] Figure 5 It is along Figure 2 The cross-sectional view taken from line I-I'.

[0022] Figure 6 It is along Figure 2 The cross-sectional view taken from line II-II'.

[0023] Figure 7 It is shown schematically. Figure 1 A partial cross-sectional view of the positive electrode layer of an all-solid-state battery.

[0024] Figure 8 It is shown schematically. Figure 1 A partial cross-sectional view of the negative electrode layer of an all-solid-state battery.

[0025] Figure 9 It is shown schematically. Figure 1 A top view of the positive electrode layer of an all-solid-state battery.

[0026] Figure 10 It is shown schematically. Figure 1 A top view of the negative electrode layer of an all-solid-state battery.

[0027] Figure 11 This is a schematic perspective view of an all-solid-state battery according to another embodiment.

[0028] Figure 12 It is shown Figure 11 A top view of an all-solid-state battery.

[0029] Figure 13 It is shown Figure 11 A bottom view of an all-solid-state battery.

[0030] Figure 14 It is along Figure 12 The cross-sectional view taken from line III-III'.

[0031] Figure 15 It is along Figure 12 The cross-sectional view taken from line IV-IV'.

[0032] Figure 16 This is a perspective view schematically showing a ring-shaped wearable electronic device on which an all-solid-state battery according to an embodiment is mounted. Detailed Implementation

[0033] The present disclosure will be described in more detail below with reference to the accompanying drawings, in which embodiments of the disclosure are illustrated. The drawings and description are to be considered illustrative rather than restrictive in nature. Throughout the specification, the same reference numerals denote corresponding elements. Additionally, in the drawings, some components are shown enlarged, omitted, or abbreviated, and the dimensions of the corresponding components do not reflect their actual dimensions.

[0034] The accompanying drawings are provided only to facilitate understanding of the embodiments disclosed in this specification and are not to be construed as limiting the spirit of the disclosure herein. It should be understood that this disclosure includes all variations, equivalents and alternatives without departing from the scope and spirit of this disclosure.

[0035] Ordinal terms such as "first," "second," etc., will be used only to describe the various components and will not be interpreted as limiting those components. These terms are only used to distinguish one component from others.

[0036] It will be understood that when an element such as a layer, film, region, area, or substrate is referred to as being "on" or "above" another element, the element may be directly on the other element, or there may be an intermediate element present. In contrast, when an element is referred to as being "directly on" another element, there is no intermediate element present. Furthermore, in the specification, the terms "on" or "above" indicate that the element is disposed on or below the target portion, and do not necessarily mean that it is disposed on the upper side of the target portion based on the direction of gravity.

[0037] Throughout this specification, it should be understood that the terms “comprising,” “including,” “having,” or “construction” indicate the presence of the features, quantities, steps, operations, components, parts, or combinations thereof described in the specification, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, operations, components, parts, or combinations thereof. Unless expressly stated to the contrary, the words “comprising” and variations such as “including” or “having” will be understood to imply the inclusion of the stated elements but not the exclusion of any other elements.

[0038] Furthermore, throughout the specification, the phrase "in a plan view" or "on a plane" indicates the target portion as viewed from the top, and the phrase "in a cross-sectional view" or "on a cross-section" describes the cross-section formed by vertically cutting the target portion as viewed from the side.

[0039] Furthermore, throughout the specification, “connection” refers not only to the case where two or more elements are directly connected, but also to the case where two or more elements are indirectly connected through other elements, and the case where two or more elements are physically or electrically connected. In addition, it may be referred to by different names depending on location or function, and may also refer to the case where corresponding components that are basically integrated are connected to each other.

[0040] Figure 1 This is a schematic perspective view of an all-solid-state battery according to an embodiment. Figure 2 It is shown Figure 1 A top view of an all-solid-state battery. Figure 3 It is shown schematically. Figure 1 A three-dimensional diagram of the stacked body, and Figure 4 It is shown schematically. Figure 1 The front view of the stacked body.

[0041] Reference Figure 1 and Figure 2 The all-solid-state battery 1000 according to this embodiment may include a laminate 100, a first external electrode 200 and a second external electrode 300.

[0042] Reference Figure 2 , Figure 3 and Figure 4 The laminate 100 may have a partially annular shape or a partially ring shape, and may include a solid electrolyte layer 110, a positive electrode layer 130 and a negative electrode layer 150.

[0043] The laminate 100 is a structure comprising a solid electrolyte layer 110, a positive electrode layer 130, and a negative electrode layer 150 stacked in the thickness direction (z-axis direction), and may have a shape that is bent around the thickness direction (z-axis direction). That is, the laminate 100 has curvature by bending in a direction intersecting the thickness direction (z-axis direction).

[0044] Here, the thickness direction (z-axis direction) can be a direction perpendicular to the wide surface (main surface) of the sheet component. For example, the thickness direction (z-axis direction) can be used as the same concept as the direction along which the components of the stacked laminate 100 are located.

[0045] The laminate 100 may include a first surface S1, a second surface S2, a third surface S3, a fourth surface S4, a fifth surface S5, and a sixth surface S6.

[0046] The first surface S1 and the second surface S2 are opposite to each other in the thickness direction (z-axis direction). That is, the first surface S1 and the second surface S2 can be arranged opposite to each other in the thickness direction (z-axis direction).

[0047] The third surface S3 can be a curved surface connecting the first surface S1 and the second surface S2, and the fourth surface S4 can be another curved surface connecting the first surface S1 and the second surface S2. Here, for ease of description, the direction of any straight line that is substantially perpendicular to the thickness direction (z-axis direction) and passes through both the third surface S3 and the fourth surface S4 will be defined as "radial". Therefore, the third surface S3 and the fourth surface S4 can be arranged radially opposite to each other.

[0048] When viewed in the thickness direction (z-axis direction), the third surface S3 and the fourth surface S4 of the laminate 100 may each have curvature. That is, the third surface S3 may have a first radius of curvature, and the fourth surface S4 may have a second radius of curvature. The second radius of curvature may be smaller than the first radius of curvature.

[0049] For example, the third surface S3 and the fourth surface S4 can be in the shape of a circular arc or an elliptical arc. As another example, the third surface S3 and the fourth surface S4 can form part of a concentric circle.

[0050] Here, for ease of description, the direction of the imaginary surface (or curve) extending between the third surface S3 and the fourth surface S4 of the laminate 100 (which intersects both the thickness direction (z-axis direction) and the radial direction) will be defined as "circumferential".

[0051] The fifth surface S5 and the sixth surface S6 can be the two end surfaces of the laminate 100 in the circumferential direction. That is, the fifth surface S5 and the sixth surface S6 can be arranged opposite to each other in the circumferential direction.

[0052] Figure 5 It is along Figure 2 The cross-sectional view taken by line I-I', and Figure 6 It is along Figure 2 The cross-sectional view taken from line II-II'.

[0053] Reference Figure 4 , Figure 5 and Figure 6 The laminate 100 may include a solid electrolyte layer 110, a positive electrode layer 130, a negative electrode layer 150, an upper protective layer 160, a lower protective layer 170, and an edge portion 180.

[0054] There can be multiple solid electrolyte layers 110, positive electrode layers 130, and negative electrode layers 150. The positive electrode layers 130 and negative electrode layers 150 can be stacked alternately in the thickness direction (z-axis direction), with the solid electrolyte layer 110 positioned between the positive electrode layer 130 and the negative electrode layer 150. This stacking structure can be repeated within the laminate 100. The electrode layer closest to the first surface S1 of the laminate 100 can be either the positive electrode layer 130 or the negative electrode layer 150, and the electrode layer closest to the second surface S2 can be either the negative electrode layer 150 or the positive electrode layer 130.

[0055] The positive electrode layer 130 may be disposed on one surface of the solid electrolyte layer 110, and the negative electrode layer 150 may be disposed on the other surface of the solid electrolyte layer 110.

[0056] The solid electrolyte layer 110 may include a solid electrolyte. The solid electrolyte can be used as a channel for lithium (Li) ions.

[0057] The solid electrolyte included in the solid electrolyte layer 110 may include a glass-ceramic electrolyte containing lithium halides (LiX, where X is a halogen element such as F, Br, Cl, I, etc.). Glass-ceramics (or microcrystalline glass) refer to a mixture of amorphous and crystalline materials that exhibit sharp and diffuse peaks in X-ray diffraction, electron beam diffraction, etc. Therefore, glass-ceramic-based electrolytes undergo partial crystallization through sintering, resulting in an electrolyte that is a mixture of amorphous and crystalline materials.

[0058] Glass-ceramic based electrolytes may include mixtures of amorphous materials and two or more types of crystalline materials. Additionally, the crystalline materials included in the glass-ceramic based electrolyte may include lithium compound crystalline phases containing lithium.

[0059] When a glass-ceramic-based electrolyte is included in the solid electrolyte layer 110, sufficient densification is achieved after sintering, thereby enabling high ionic conductivity.

[0060] For example, glass-ceramic electrolytes may include lithium (Li) oxide, boron (B) oxide, silicon (Si) oxide, aluminum (Al) oxide, gallium (Ga) oxide, phosphorus (P) oxide, germanium (Ge) oxide, magnesium (Mg) oxide, and lithium chloride (LiCl). As a specific example, a glass-ceramic electrolyte may include Li₂O-B₂O₃-SiO₂-P₂O₅-GeO₂-LiCl.

[0061] As another example, the solid electrolyte included in the solid electrolyte layer 110 may comprise a lithium borosilicate-based electrolyte (hereinafter referred to as LBSO-based electrolyte). LBSO-based electrolyte is a glassy electrolyte, and glass refers to a crystallographically amorphous material with diffuse peaks observed in X-ray diffraction or electron beam diffraction.

[0062] When an LBSO-based electrolyte is included in the solid electrolyte layer 110, the amorphous state can be maintained during sintering while lowering the sintering temperature. Therefore, it offers the advantages of achieving high ionic conductivity and low reactivity with the electrodes. The LBSO-based electrolyte may include lithium (Li), boron (B), silicon (Si), aluminum (Al), phosphorus (P), germanium (Ge), and sulfur (S).

[0063] Optionally, the solid electrolyte included in the solid electrolyte layer 110 may be one or more types selected from the group consisting of garnet type, Na superionic conductor (NASICON type), lithium superionic conductor (LISICON type), perovskite type and lithium phosphorus oxynitride (LiPON type).

[0064] In the region provided with the edge portion 180 which will be described later, a material having low ionic conductivity and low electronic conductivity (i.e., an insulating material) may be present, or a material having ionic conductivity (or electronic conductivity) approximate to the ionic conductivity (or electronic conductivity) of the solid electrolyte may be present. For example, when a material having ionic conductivity (or electronic conductivity) approximate to the ionic conductivity (or electronic conductivity) of the solid electrolyte is present in the edge portion, the material may be the same as or different from the solid electrolyte in other regions. In another example, the material having ionic conductivity (or electronic conductivity) approximate to the ionic conductivity (or electronic conductivity) of the solid electrolyte and the insulating material may coexist in the edge portion.

[0065] The garnet-type solid electrolyte may refer to Li a La b Zr c O 12 (such as Li7La3Zr2O 12 ) represented lithium lanthanum zirconium oxide (LLZO), and the NASICON-type solid electrolyte may include lithium aluminum titanium phosphate (LATP) (Li 1+x Al x M 2-x (PO4)3 (LAMP) (where 0<x<2, M is Zr, Ti or Ge) generated by introducing Ti into the type compound, (where 0<x<1), lithium aluminum germanium phosphate (LAGP) represented by Li containing excess lithium 1+x Al x Ti 2-x (PO4)3 (where 0<x<1) (such as Li 1+x Al x Ge 2-x (PO4)3 (where 0<x<1) (such as Li 1.3 Al 0.3 Ge 1.7 (PO4)3) and / or lithium zirconium phosphate (LZP) (LiZr2(PO4)3).

[0066] In addition, the LISICON-type solid electrolyte may include: a solid solution oxide represented by xLi3AO4-(1-x)Li4BO4 (where A is P, As, V, etc., and B is Si, Ge, Ti, etc.), such as Li 14 Zn(GeO4)4, Li 10 GeP2O 12 (LGPO), Li 3.5 Si 0.5 P 0.5 O4 and Li 10.42 Si(Ge) 1.5 P 1.5 Cl0.08 O 11.92 and the like; and a solid solution sulfide represented by Li 4-x M 1-y M' y S4 (where M is Si or Ge, and M' is P, Al, Zn or Ga), such as Li2S-P2S5, Li2S-SiS2, Li2S-SiS2-P2S5 or Li2S-GeS2.

[0067] In addition, the perovskite-type solid electrolyte may include lithium lanthanum titanate (LLTO) represented by Li 3x La 2 / 3-x □ 1 / 3-2x TiO3 (where 0<x<0.16, and □ is a vacancy) (such as Li 1 / 8 La 5 / 8 TiO3), and the LiPON-type solid electrolyte may include a nitride such as lithium phosphorus oxynitride (Li 2.8 PO 3.3 N 0.46 ) and the like.

[0068] The positive electrode layer 130 may be exposed to the outside of the laminate 100 from the fifth surface S5, and may be connected to the first external electrode 200.

[0069] Figure 7 is a schematic partial cross-sectional view showing Figure 1 the positive electrode layer of the all-solid-state battery.

[0070] Referring to Figure 7 , the positive electrode layer 130 may include a positive electrode current collector 133, a first positive electrode active material layer 135, and a second positive electrode active material layer 136.

[0071] For example, the positive electrode current collector 133 may be made of a plate-shaped member or a thin member. As another example, the positive electrode current collector 133 may be a porous body having a network shape, a mesh shape, or the like.

[0072] The positive electrode current collector 133 may include a first surface 133a and a second surface 133b that face each other in the thickness direction (z-axis direction). The positive electrode current collector 133 may include, but is not limited to, a porous metal plate made of stainless steel, nickel (Ni), copper (Cu), tin (Sn), aluminum (Al), or an alloy thereof.

[0073] In addition, the positive electrode current collector 133 may be coated with an oxidation-resistant metal or an oxidation-resistant alloy film to prevent oxidation.

[0074] The positive electrode current collector 133 may include a carbon substrate-like component, a thin component, or a linear component. The positive electrode current collector 133 may include a conductive carbon material. The conductive carbon material may include graphite, conductive fibers (such as carbon nanotubes (CNTs) or vapor-grown carbon fibers (VGCF)) or conductive carbon (such as carbon black).

[0075] In addition, the positive electrode current collector may also include one or more types of solid electrolytes.

[0076] The first positive electrode active material layer 135 and the second positive electrode active material layer 136 may include positive electrode active material and may be disposed on the surface of the positive electrode current collector 133. The first positive electrode active material layer 135 and the second positive electrode active material layer 136 may be formed by printing positive electrode active material on one or both surfaces of the positive electrode current collector 133, but the method for forming the positive electrode active material layer is not limited thereto.

[0077] The positive electrode active material included in the positive electrode active material layers 135 and 136 may include a material containing lithium (Li) ions. The positive electrode active material can reversibly insert and extract lithium ions. In other words, the positive electrode active material may contain lithium ions and be used to supply lithium ions to the negative electrode during charging of the all-solid-state battery. The positive electrode active material can affect the capacity and output of the all-solid-state battery.

[0078] For example, the positive electrode active material may include at least one selected from the group consisting of compounds represented by the following formula: Li a A 1-b M b D2 (where 0.90≤a≤1.8, 0≤b≤0.5); Li a E 1-b M b O 2-c D c (Where, 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); LiE 2-b M b O 4-c D c (Where, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05); Li a Ni 1-b-c Co b M c D α (Where, 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Co b M c O 2-α X α(Where, 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Co b M c O 2-α X2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b M c D α (Where, 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Mn b M c O 2-α X α (Where, 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b M c O 2-α X2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni b E c G d O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0.001≤e≤0.1); Li a NiG b O2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a MnG b O2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn2G bO4 (where 0.90≤a≤1.8, 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O2; LiRO2; LiNiVO4; Li (3-f) J2(PO4)3 (0≤f≤2); Li (3-f) Fe2(PO4)3 (where 0≤f≤2) and LiFePO4, wherein, in the above formula, A is Ni, Co or Mn; M is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, Nb, Ti or rare earth element; D is O, F, S or P; E is Co or Mn; X is F, S or P; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr or V; Q is Ti, Mo or Mn; R is Cr, V, Fe, Sc or Y; and J is V, Cr, Mn, Co, Ni or Cu.

[0079] In addition, positive electrode active materials may also include LiCoO2 and LiMn. x O 2x (where x is 1 or 2), LiNi 1-x Mn x O 2x (where 0) <x<1)、LiNi 1-x-y Co x Mn y O2 (where 0≤x≤0.5, 0≤y≤0.5), LiFePO4, TiS2, FeS2, TiS3 or FeS3, but not limited to these.

[0080] The positive electrode active material may optionally include a conductive material and a binder. However, because organic substances such as binders decompose during the sintering process, the organic material may not remain on the positive electrode active material layer of the obtained positive electrode current collector.

[0081] There are no particular restrictions on the conductive materials, as long as they are conductive and do not cause chemical changes in the all-solid-state battery 1000. For example, the following materials can be used: graphite, such as natural and artificial graphite; carbon-based materials, such as carbon black, acetylene black, and Ketjen black. ® Channel black, furnace black, lamp black, and pyrolysis black; conductive fibers, such as carbon fibers and metal fibers; fluorides; metallic components (such as lithium (Li), tin (Sn), aluminum (Al), nickel (Ni), copper (Cu), etc.), oxides of said metallic components, nitrides of said metallic components, or fluorides of said metallic components; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives.

[0082] Adhesives can be used to improve the bonding strength of active materials, conductive materials, etc. Adhesives may include, but are not limited to, at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers.

[0083] In addition, the positive electrode layer 130 may also contain a solid electrolyte component. The solid electrolyte component may contain one or more of the components mentioned above and can serve as an ion conduction channel in the positive electrode layer. Therefore, the interfacial resistance can be reduced.

[0084] Figure 9 It is shown schematically. Figure 1 A top view of the positive electrode layer of an all-solid-state battery.

[0085] Reference Figure 9 The positive electrode layer 130 has a shape corresponding to the shape of the laminate 100. That is, the positive electrode layer 130 has a partially annular shape or a partially ring-shaped shape.

[0086] Except for the portion of the positive electrode layer 130 connected to the first external electrode 200, the edge of the positive electrode layer 130 may be spaced apart from the edge of the laminate 100, and the edge portion 180 may be disposed in the space between the edge of the positive electrode layer 130 and the edge of the laminate 100.

[0087] The negative electrode layer 150 may be exposed on the outside of the laminate 100 from the sixth surface S6 and may be connected to the second external electrode 300.

[0088] Figure 8 It is shown schematically. Figure 1 A partial cross-sectional view of the negative electrode layer of an all-solid-state battery.

[0089] Reference Figure 8 The negative electrode layer 150 may include a negative electrode current collector 153, a first negative electrode active material layer 155, and a second negative electrode active material layer 156.

[0090] For example, the negative electrode current collector 153 may be formed using a plate-like member or a thin member. As another example, the negative electrode current collector 153 may include a porous body having a network-like, mesh-like, or similar structure.

[0091] The negative electrode current collector 153 may include a first surface 153a and a second surface 153b. The first surface 153a and the second surface 153b are opposite to each other in the thickness direction (z-axis direction).

[0092] For example, the negative current collector 153 may include, but is not limited to, a porous metal plate made of stainless steel, nickel (Ni), copper (Cu), tin (Sn), aluminum (Al), or an alloy thereof.

[0093] In addition, the negative current collector 153 may be coated with an oxidation-resistant metal or an oxidation-resistant alloy film to prevent oxidation.

[0094] Similar to the positive current collector 133, the negative current collector 153 may include a conductive carbon-based material, and may include one or more types of solid electrolytes. The negative current collector 153 may be the same as the negative active material layers 155 and 156.

[0095] The first negative active material layer 155 and the second negative active material layer 156 may include a negative active material, and may be disposed on the surface of the negative current collector 153. The first negative active material layer 155 and the second negative active material layer 156 may be formed by printing the negative active material on one surface or both surfaces of the negative current collector 153. However, the method for forming the negative active material layer is not limited to printing.

[0096] The negative active material included in the negative active material layers 155 and 156 may store lithium ions that have moved from the positive electrode and release the lithium ions during discharging of the all-solid-state battery, thereby generating electrical energy. A carbon-based material, silicon, silicon oxide, a silicon-based alloy, a silicon-carbon-based material composite, tin, a tin-based alloy, a tin-carbon composite, a metal oxide, or a combination thereof may be used as the negative active material. The negative active material may include lithium metal and / or a lithium metal alloy.

[0097] The lithium metal alloy may include lithium and a metal / metalloid capable of forming an alloy with lithium. For example, the metal / metalloid capable of forming an alloy with lithium may include Si, Sn, Al, Ge, Pb, Bi, Sb, a Si-AM alloy (where AM is an alkali metal, an alkaline earth metal, an element from Groups 13 to 16, a transition metal, a rare earth element, or a combination thereof, and excludes Si), a Sn-AM alloy (where AM is an alkali metal, an alkaline earth metal, an element from Groups 13 to 16, a transition metal, a transition metal oxide such as lithium titanium oxide (Li4Ti5O 12 )), a rare earth element, or a combination thereof, and excludes Sn), MnO x (where 0<x≤2), and the like.

[0098] Element AM may include Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof.

[0099] In addition, the oxide of a metal / metalloid capable of forming an alloy with lithium may include lithium titanium oxide, vanadium oxide, lithium vanadium oxide, SnO₂, SiO x (where 0<x<2), and the like. For example, the negative active material may include one or more elements selected from the group consisting of elements in Groups 13 to 16 of the Periodic Table of the Elements. For example, the negative active material may include one or more elements selected from the group consisting of Si, Ge and Sn.

[0100] The carbon-based material may include crystalline carbon, amorphous carbon, or a mixture thereof. The crystalline carbon may be graphite (such as natural graphite or artificial graphite), and the graphite is in an amorphous form, a disk form, a flake form, a spherical form, or a fibrous form. In addition, the amorphous carbon may include, but is not limited to, soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, calcined coke, graphene, carbon black, fullerene soot, carbon nanotubes, carbon fiber, and the like.

[0101] Silicon may include at least one selected from the group consisting of Si, SiO x (where 0<x<2, for example, 0.5 to 1.5), Sn, SnO₂, or a silicon-containing metal alloy, and mixtures thereof. For example, the silicon-containing metal alloy may include silicon and one or more of Al, Sn, Ag, Fe, Bi, Mg, Zn, In, Ge, Pb, or Ti.

[0102] The negative active material may optionally include a conductive material and a binder.

[0103] The conductive material is not particularly limited as long as it has electrical conductivity and does not cause chemical changes in the all-solid-state battery 1000. For example, the following materials may be used: graphite, such as natural graphite and artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black ®Channel black, furnace black, lamp black, and pyrolysis black; conductive fibers, such as carbon fibers and metal fibers; fluorides; metallic components (such as lithium (Li), tin (Sn), aluminum (Al), nickel (Ni), copper (Cu), etc.), oxides of said metallic components, nitrides of said metallic components, or fluorides of said metallic components; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives.

[0104] Adhesives can be used to improve the bonding strength of active materials, conductive materials, etc. Adhesives may include, but are not limited to, at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers.

[0105] In addition, the negative electrode layer 150 may also contain a solid electrolyte component. The solid electrolyte component may contain one or more of the components mentioned above and can serve as an ion conduction channel in the negative electrode layer. Therefore, the interfacial resistance can be reduced.

[0106] Figure 10 It is shown schematically. Figure 1 A top view of the negative electrode layer of an all-solid-state battery.

[0107] Reference Figure 10 The negative electrode layer 150 may have a shape corresponding to the shape of the laminate 100. That is, the negative electrode layer 150 may have a partially annular shape or a partially ring shape.

[0108] Except for the portion of the negative electrode layer 150 connected to the second external electrode 300, the edge of the negative electrode layer 150 may be spaced apart from the edge of the laminate 100, and the edge portion 180 may be disposed in the space between the edge of the negative electrode layer 150 and the edge of the laminate 100.

[0109] Reference Figure 4 , Figure 5 and Figure 6 The upper protective layer 160 and the lower protective layer 170 can be the outermost layers facing the first surface S1 and the second surface S2 of the laminate 100, respectively. That is, the upper protective layer 160 can be the outermost layer facing the first surface S1 of the laminate 100, and the lower protective layer 170 can be the outermost layer facing the second surface S2 of the laminate 100. The upper protective layer 160 and the lower protective layer 170 can improve moisture resistance by preventing moisture penetration and can also prevent damage caused by physical impacts and chemical effects.

[0110] The upper protective layer 160 and the lower protective layer 170 may be insulating layers made of insulating materials (i.e., materials that do not have electronic conductivity (ionic conductivity)).

[0111] The upper protective layer 160 and the lower protective layer 170 may comprise ceramic materials, such as alumina (Al2O3), aluminum nitride (AlN), beryllium oxide (BeO), boron nitride (BN), silicon (Si), silicon carbide (SiC), silicon dioxide (SiO2), silicon nitride (Si3N4), gallium arsenide (GaAs), gallium nitride (GaN), barium titanate (BaTiO3), zirconium dioxide (ZrO2), mixtures thereof, oxides and / or nitrides of such materials, or any other suitable ceramic material, but not limited thereto. Additionally, the upper protective layer 160 and the lower protective layer 170 may selectively comprise the aforementioned solid electrolytes, and may comprise one or more types of solid electrolytes, but are not limited thereto.

[0112] Edge portion 180 may be provided along the edges of positive electrode layer 130 and negative electrode layer 150. Edge portion 180 may be configured to contact the remaining edges of positive electrode layer 130 except for the positive electrode layer 130 being connected to the first external electrode 200. In addition, edge portion 180 may be configured to contact the remaining edges of negative electrode layer 150 except for the negative electrode layer 150 being connected to the second external electrode 300.

[0113] For example, the edge portion 180 may be located on the solid electrolyte layer 110 and in a region other than the regions where the positive electrode layer 130 and the negative electrode layer 150 are disposed. When the positive electrode layer 130 is located on the solid electrolyte layer 110, the edge portion 180 may be located in a region other than the region where the positive electrode layer 130 is disposed. Similarly, when the negative electrode layer 150 is located on the solid electrolyte layer 110, the edge portion 180 may be located in a region other than the region where the negative electrode layer 150 is disposed.

[0114] Reference Figure 5 and Figure 6 The edge portion 180 may constitute a part of the fifth surface S5 and a part of the sixth surface S6 of the laminate 100. Additionally, refer to... Figure 9 and Figure 10 The edge portion 180 may form part of the third surface S3 and part of the fourth surface S4 of the laminate 100.

[0115] The edge portion 180 can be configured to compensate for the height difference between the solid electrolyte layer 110 and the positive electrode layer 130, and the height difference between the solid electrolyte layer 110 and the negative electrode layer 150. For example, the edge portion 180 can be disposed on the same surface as the positive electrode layer 130, and the edge portion 180 can be disposed on the same surface as the negative electrode layer 150. The edge portion 180 can compensate for the height difference between the solid electrolyte layer 110 and the positive electrode layer 130, or the height difference between the solid electrolyte layer 110 and the negative electrode layer 150. This improves the density between the solid electrolyte layer 110 and the electrode layers, preventing interlayer delamination or warping caused by sintering during the manufacturing process of all-solid-state batteries.

[0116] Additionally, the edge portion 180 can be made of a material that is moisture-resistant and has low lithium (Li) ion conductivity. In this case, the edge portion 180 can protect the active material layers 135, 136, 155, and 156 from moisture penetration or lithium (Li) ion leakage. For example, the edge portion 180 may include an insulating material or an electrolyte material, and may include an ion conductivity of less than or equal to 1.0 × 10⁻⁶. -10 Materials with S / cm.

[0117] The edge portion 180 may include an insulating material (i.e., a material that does not have electronic conductivity (ionic conductivity)).

[0118] The edge portion 180 may include ceramic materials, such as alumina (Al2O3), aluminum nitride (AlN), beryllium oxide (BeO), boron nitride (BN), silicon (Si), silicon carbide (SiC), silicon dioxide (SiO2), silicon nitride (Si3N4), gallium arsenide (GaAs), gallium nitride (GaN), barium titanate (BaTiO3), zirconium dioxide (ZrO2), mixtures thereof, oxides and / or nitrides of these materials, or any other suitable ceramic material, but not limited thereto.

[0119] Additionally, the edge portion 180 may optionally include a solid electrolyte that is the same as or different from the solid electrolyte included in the solid electrolyte layer described above, and may include one or more types of solid electrolytes, but is not limited thereto.

[0120] Additionally, the edge portion 180 may contain a material with low ionic conductivity and low electronic conductivity (i.e., an insulating material), or it may contain a material with ionic conductivity (or electronic conductivity) similar to that of the solid electrolyte. For example, when a material with ionic conductivity (or electronic conductivity) similar to that of the solid electrolyte is present in the edge portion, this material may be the same as or different from the solid electrolyte in other regions. In another example, a material with ionic conductivity (or electronic conductivity) similar to that of the solid electrolyte and an insulating material may coexist in the edge portion.

[0121] Reference Figure 1 and Figure 2 The first external electrode 200 and the second external electrode 300 may be located outside the laminate 100.

[0122] Reference Figure 5 The first external electrode 200 is connected to the positive electrode layer 130 and the solid electrolyte layer 110 on the fifth surface S5 of the laminate 100. For example, the first external electrode 200 may cover the fifth surface S5 of the laminate 100, and the first external electrode 200 may extend to the first surface S1, the second surface S2, the third surface S3 and the fourth surface S4 of the laminate 100 to partially cover the respective surfaces.

[0123] The first external electrode 200 can be formed by calcining a conductive paste. For example, the conductive paste may include glass and metals such as silver (Ag) or copper (Cu).

[0124] Reference Figure 6 The second external electrode 300 can be connected to the negative electrode layer 150 and the solid electrolyte layer 110 on the sixth surface S6 of the laminate 100. For example, the second external electrode 300 can cover the sixth surface S6 of the laminate 100, and the second external electrode 300 can extend to the first surface S1, the second surface S2, the third surface S3 and the fourth surface S4 of the laminate 100 to partially cover the respective surfaces.

[0125] The second external electrode 300 can be formed by calcining a conductive paste. For example, the conductive paste may include glass and metals such as silver (Ag) or copper (Cu).

[0126] For example, the fifth surface S5 and the sixth surface S6 of the laminate 100 are immersed in conductive paste and then dried to form the first external electrode 200 and the second external electrode 300. As another example, conductive paste can be applied to the fifth surface S5 and the sixth surface S6 of the laminate 100 to form the first external electrode 200 and the second external electrode 300. As yet another example, a dry film obtained by drying the conductive paste can be transferred to the laminate 100 and then calcined to form the first external electrode 200 and the second external electrode 300, but the method of forming the first external electrode 200 and the second external electrode 300 is not limited to the methods described above. For example, the conductive metal in the conductive paste may include at least one of copper (Cu), nickel (Ni), tin (Sn), palladium (Pd), platinum (Pt), gold (Au), silver (Ag), tungsten (W), titanium (Ti), lead (Pb), or alloys thereof, but is not limited to these.

[0127] Figure 11 This is a schematic perspective view of an all-solid-state battery according to another embodiment. Figure 12 It is shown Figure 11 A top view of an all-solid-state battery, and Figure 13 It is shown Figure 11 A bottom view of the all-solid-state battery. Additionally... Figure 14 It is along Figure 12 The cross-sectional view taken from line III-III', and Figure 15 It is along Figure 12 The cross-sectional view taken from line IV-IV'.

[0128] Reference Figure 11 , Figure 12 , Figure 13 , Figure 14 and Figure 15 The all-solid-state battery 2000 may include a stack 1100, a first external electrode 1200, a second external electrode 1300, a first insulating layer 910, and a second insulating layer 920.

[0129] The laminate 1100 may have a partially annular shape or a partially ring shape, and may include a solid electrolyte layer 110, a positive electrode layer 130, and a negative electrode layer 150.

[0130] The first external electrode 1200 may include a first connecting portion 1210 and a first lead-out portion 1220.

[0131] The first connecting part 1210 may be disposed on the fifth surface S5 of the laminate 1100 and may be connected to the positive electrode layer 130 and the solid electrolyte layer 110.

[0132] For example, the first connection portion 1210 may be a thin film of metal. For example, the first connection portion 1210 may be formed by sputtering a thin film of metal on the fifth surface S5 of the laminate 1100. Here, the thin film of metal may include Pt, Ag, Au, Ni, Cr or combinations thereof.

[0133] As another example, the first connection portion 1210 can be formed by calcining a conductive paste. The conductive paste may include, for example, glass and conductive metals such as silver (Ag) or copper (Cu).

[0134] One end of the first connecting portion 1210 in the thickness direction (z-axis direction) may be spaced apart from the first surface S1 of the laminate 1100. For example, the first connecting portion 1210 may expose a portion of the upper protective layer 160 or the uppermost solid electrolyte layer 110 on the fifth surface S5.

[0135] The other end of the first connecting portion 1210 in the thickness direction (z-axis direction) can extend to the second surface S2. Specifically, the first connecting portion 1210 can completely cover the lower protective layer 170 on the fifth surface S5.

[0136] The first lead-out portion 1220 may extend from the first connecting portion 1210 to the second surface S2 of the laminate 1100. The first lead-out portion 1220 may cover a portion of the second surface S2 of the laminate 1100.

[0137] The first lead-out portion 1220 can be formed by calcining a conductive paste. The conductive paste may include, for example, glass and conductive metals such as silver (Ag) or copper (Cu).

[0138] The first insulating layer 910 may cover a portion of the protective layer 160 and the first connecting portion 1210 on the fifth surface S5 of the laminate 1100.

[0139] The first insulating layer 910 may include a ceramic material. For example, the first insulating layer 910 may include aluminum oxide (Al2O3), aluminum nitride (AlN), beryllium oxide (BeO), boron nitride (BN), silicon (Si), silicon carbide (SiC), silicon dioxide (SiO2), silicon nitride (Si3N4), gallium arsenide (GaAs), gallium nitride (GaN), barium titanate (BaTiO3), zirconium dioxide (ZrO2), mixtures thereof, oxides and / or nitrides of these materials, or any other suitable ceramic material, but is not limited thereto.

[0140] The second external electrode 1300 may include a second connecting portion 1310 and a second lead-out portion 1320.

[0141] The second connecting part 1310 may be provided on the sixth surface S6 of the laminate 1100 and may be connected to the negative electrode layer 150 and the solid electrolyte layer 110.

[0142] For example, the second connection portion 1310 may be a thin film of metal. For example, the second connection portion 1310 may be formed by sputtering a thin film of metal on the sixth surface S6 of the laminate 1100. Here, the thin film of metal may include Pt, Ag, Au, Ni, Cr or combinations thereof.

[0143] As another example, the second connection 1310 can be formed by calcining a conductive paste. The conductive paste may include, for example, glass and conductive metals such as silver (Ag) or copper (Cu).

[0144] One end of the second connecting portion 1310 in the thickness direction (z-axis direction) may be spaced apart from the first surface S1 of the laminate 1100. For example, the second connecting portion 1310 may expose a portion of the upper protective layer 160 or the uppermost solid electrolyte layer 110 on the sixth surface S6.

[0145] The other end of the second connecting portion 1310 in the thickness direction (z-axis direction) may extend to the second surface S2. Specifically, the second connecting portion 1310 may cover the sixth surface S6 with a lower protective layer 170.

[0146] The second lead-out portion 1320 may extend from the second connecting portion 1310 to the second surface S2 of the laminate 1100. The second lead-out portion 1320 may cover a portion of the second surface S2 of the laminate 1100.

[0147] The second lead-out portion 1320 can be formed by calcining a conductive paste. The conductive paste may include, for example, glass and conductive metals such as silver (Ag) or copper (Cu).

[0148] The second insulating layer 920 may cover a portion of the protective layer 160 and the second connecting portion 1310 on the sixth surface S6 of the laminate 1100.

[0149] The second insulating layer 920 may include a ceramic material. For example, the second insulating layer 920 may include aluminum oxide (Al2O3), aluminum nitride (AlN), beryllium oxide (BeO), boron nitride (BN), silicon (Si), silicon carbide (SiC), silicon dioxide (SiO2), silicon nitride (Si3N4), gallium arsenide (GaAs), gallium nitride (GaN), barium titanate (BaTiO3), zirconium dioxide (ZrO2), mixtures thereof, oxides and / or nitrides of these materials, or any other suitable ceramic material, but this embodiment is not limited thereto.

[0150] Other components besides those mentioned above Figure 1 The components of the all-solid-state batteries represented herein are the same or corresponding, and repeated descriptions of them will be omitted.

[0151] Figure 16 This is a perspective view schematically showing a ring-shaped wearable electronic device on which an all-solid-state battery according to an embodiment is mounted.

[0152] Reference Figure 16 The all-solid-state battery 1000 can be installed inside the ring-shaped wearable electronic device 3000. Like other components 3100, the shape of the all-solid-state battery 1000 corresponds to the shape of the ring-shaped wearable electronic device 3000, so that the all-solid-state battery 1000 can be installed on the ring-shaped wearable electronic device 3000 without wasting space.

[0153] While this disclosure has been described in conjunction with what are now considered to be actual embodiments, it should be understood that this disclosure is not limited to these embodiments. Rather, this disclosure is intended to cover various variations and equivalents within the spirit and scope of the appended claims.

[0154] <Explanation of reference numerals in the attached figures> 1000, 2000: All-solid-state batteries 100, 1100: Layered bodies 110: Solid electrolyte layer 130: Positive electrode layer 150: Negative electrode layer 160: Upper protective layer 170: Lower protective layer 180: Edge 200, 1200: First external electrode 300, 1300 Second External Electrode 910: First insulating layer 920: Second insulating layer.

Claims

1. An all-solid-state battery, comprising: A laminate comprising a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in a first direction; The first external electrode is disposed outside the laminate and connected to the positive electrode layer; as well as The second external electrode is disposed outside the laminate and connected to the negative electrode layer. The positive electrode layer includes a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer is disposed on the positive electrode current collector and is in contact with the solid electrolyte layer. The negative electrode layer includes a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is disposed on the negative electrode current collector and in contact with the solid electrolyte layer. The laminated body is bent in a second direction that intersects with the first direction.

2. The all-solid-state battery according to claim 1, wherein, The laminate has curvature.

3. The all-solid-state battery according to claim 2, wherein, The laminate includes a first surface and a second surface disposed opposite to each other in the second direction. The first surface has a first radius of curvature, and The second surface has a second radius of curvature.

4. The all-solid-state battery according to claim 3, wherein, The first radius of curvature is smaller than the second radius of curvature.

5. The all-solid-state battery according to claim 4, wherein, When viewed along the first direction, the first surface and the second surface form a circular arc shape or an elliptical arc shape.

6. The all-solid-state battery according to claim 4, wherein, When viewed along the first direction, the first surface and the second surface form part of a concentric circle.

7. The all-solid-state battery according to claim 2, wherein, The positive electrode layer, the solid electrolyte layer, and the negative electrode layer each have the same curvature as the laminate.

8. The all-solid-state battery according to claim 3, wherein, The laminate includes a first end surface and a second end surface disposed opposite to each other along a third direction, the third direction intersecting the first direction and the second direction and extending between the first surface and the second surface. The first external electrode is disposed on the first end surface, and The second external electrode is disposed on the second end surface.

9. The all-solid-state battery according to claim 8, wherein, The laminate includes a third surface and a fourth surface disposed opposite to each other in the first direction. The first external electrode extends from the first end surface to cover a portion of the third surface and a portion of the fourth surface, and The second external electrode extends from the second end surface to cover a portion of the third surface and a portion of the fourth surface.

10. The all-solid-state battery according to claim 3, wherein, The laminate includes: a first end surface and a second end surface disposed opposite to each other along a third direction, the third direction intersecting the first direction and the second direction and extending between the first surface and the second surface; and a third surface and a fourth surface disposed opposite to each other along the first direction. The first external electrode includes a first connecting portion disposed on the first end surface and a first lead-out portion connected to the first connecting portion and located on the fourth surface. The second external electrode includes a second connecting portion disposed on the second end surface and a second lead-out portion connected to the second connecting portion and located on the fourth surface.

11. The all-solid-state battery according to claim 10, further comprising: A first insulating layer covers the first connection portion on the first end surface; as well as A second insulating layer covers the second connection portion on the second end surface.

12. An all-solid-state battery, comprising: A laminate comprising a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in a first direction; The edge portion is provided along the edge of the positive electrode layer and the edge of the negative electrode layer; The first external electrode is disposed on the first end surface of the laminate and connected to the positive electrode layer; The second external electrode is disposed on the second end surface of the laminate and connected to the negative electrode layer; as well as A first insulating layer and a second insulating layer, wherein the first insulating layer covers the first external electrode on the first end surface, and the second insulating layer covers the second external electrode on the second end surface. The edge portion is made of an insulating material with low ionic conductivity.

13. The all-solid-state battery according to claim 12, wherein, The edge portion comprises a material selected from the group consisting of alumina (Al2O3), silicon carbide (SiC), boron nitride (BN), and zirconium dioxide (ZrO2).

14. The all-solid-state battery according to claim 13, wherein, The ionic conductivity of the edge portion is less than or equal to 1.0 × 10⁻⁶. -10 S / cm.